THERMAL-PHYSICAL PROCESSES AT HEATING OF METAL IN ANNULAR FURNACES - V. I. Timoshpolskij; Ju. A. Samojlovich; O. G. Hopova (Литьë и металлургия, 2005)
In the article there are presented the materials, concerning the peculiarities of thermal-physical processes, occurring at heating of cylindrical slugs in circular furnaces. The methods of calculation of actual heat capacity and cubic density, enabling to receive more precise results in comparison to the known ones, are worked out.